The development of an information management system for materials management in large construction companies operating in the Ghanaian construction industry - Manteau, Eric Kofi (2011)
A project report presented to the Department of Building Technology of the Faculty of Architecture and Building Technology in partial fulfilment of the requirements for a degree of Master of Science in Construction Management.